Longitudinal monitoring of sewershed resistomes in socioeconomically diverse urban neighborhoods - Jangwoo Lee; Kevin Xiang; Emily Au; Shahrzad Sarabi; Nicole Acosta; Srijak Bhatnagar; Jennifer Van Doorn; Stefania Bertazzon; John M. Conly; Elissa Rennert-May; Johann D. D. Pitout; Bonita E. Lee; et al. (Communications Medicine)
Abstract Background Understanding factors associated with antimicrobial resistance (AMR) distribution across populations is a necessary step in planning mitigation measures. While associations between AMR and socioeconomic-status (SES), including employment and education have been increasingly recognized in low- and middle-income settings, connections are less clear in high-income countries where SES remains an important influence on other health outcomes. Methods We explored the relationship between SES and AMR in Calgary, Canada using spatially-resolved wastewater-based surveillance of resistomes detected by metagenomics across eight socio-economically diverse urban neighborhoods. Resistomes were established by shotgun-sequencing of wastewater pellets, and qPCR of targeted-AMR genes. SES status was established using 2021 Canadian census data. Conducting this comparison during the height of COVID-related international travel restrictions (Dec. 2020–Oct. 2021) allowed the hypotheses linking SES and AMR to be assessed with limited confounding. These were compared with sewage metagenomes from 244 cities around the world, linked with Human Development Index (HDI). Results Wastewater metagenomes from Calgary’s socioeconomically diverse neighborhoods exhibit highly similar resistomes, with no quantitative differences (p > 0.05), low Bray-Curtis dissimilarity, and no significant correlations with SES. By comparison, dissimilarity is observed between globally-sourced resistomes (p < 0.05), underscoring the homogeneity of resistomes in Calgary’s sub-populations. The analysis of globally-sourced resistomes alongside Calgary’s resistome further reveals lower AMR burden in Calgary relative to other cities around the world. This is particularly pronounced for the most clinically-relevant AMR genes (e.g., beta-lactamases, macrolide-lincosamide-streptogramin). Conclusions This work showcases the effectiveness of inclusive and comprehensive wastewater-based surveillance for exploring the interplay between SES and AMR.